2006
DOI: 10.1007/bf03192391
|View full text |Cite
|
Sign up to set email alerts
|

A maximum uncertainty LDA-based approach for limited sample size problems — with application to face recognition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
0
19
0
4
Order By: Relevance
“…FLD can be easily extended to multi-class cases via multiple discriminant analysis [41]. In fact, discriminant analysis has been widely used in this way in pattern recognition problems, and its use in reducing facial recognition problems is well documented [42]. This has been the motivation to use discriminant analysis for multiple distinct binary classifications.…”
Section: A the Lda Based Classifiermentioning
confidence: 99%
“…FLD can be easily extended to multi-class cases via multiple discriminant analysis [41]. In fact, discriminant analysis has been widely used in this way in pattern recognition problems, and its use in reducing facial recognition problems is well documented [42]. This has been the motivation to use discriminant analysis for multiple distinct binary classifications.…”
Section: A the Lda Based Classifiermentioning
confidence: 99%
“…To avoid both critical issues, we have calculated w lda by using a maximum uncertainty LDA-based approach (MLDA) that considers the issue of stabilizing the S w estimate with a multiple of the identity matrix [26,25,27].…”
Section: Linear Discriminant Analysis (Lda)mentioning
confidence: 99%
“…We review the theory behind the cited methods, their common points, and discuss why SVM is in general the best technique for classification but not necessarily the best for extracting discriminant information. This will be discussed using face images and the separating hyperplanes generated by SVM [30,14,28] and a regularized version of LDA called Maximum uncertainty Linear Discriminant Analysis (MLDA) [27]. To further evaluate DFA on a data set not composed of images, we investigate a breast lesion classification framework, proposed in [17], that uses ultrasound features and SVM only.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the aforementioned critical issues of the standard LDA in limited sample and high dimensional problems, we have calculated lda P by using a maximum uncertainty LDA-based approach (MLDA) that considers the issue of stabilising the w S estimate with a multiple of the identity matrix [8,9]. In a previous study [8] with application to the face recognition problem, Thomaz and Gillies showed that the MLDA approach improved the LDA classification performance with or without a PCA intermediate step and using less linear discriminant features [8].…”
Section: Maximum Uncertainty Lda (Mlda)mentioning
confidence: 99%
“…Analogously to the Cootes et al approaches [1 -4], SDM requires a previous alignment of all the images to a common template to minimise variations that are not necessarily related to differences between the faces. However, instead of using landmarks or annotations on the images, SDM is based on the idea of using PCA to reduce the dimensionality of the original images and a maximum uncertainty linear classifier (MLDA) [8] to characterise the most discriminant differences between the samples of images.…”
Section: Introductionmentioning
confidence: 99%